1990
DOI: 10.1037/h0079201
|View full text |Cite
|
Sign up to set email alerts
|

Children and their fathers after parental separation.

Abstract: This two-year longitudinal study of 121 6-12-year-old children in the custody of their mothers following parental separation examined main and interacting effects of child's age and gender, frequency and regularity of visitation, father-child closeness, and parental legal conflict on children's self-esteem and behavioral adjustment at two time points. Predictors were found to have different implications for different groups of children and for children in different situations. Findings suggest the futility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
4

Year Published

1993
1993
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 30 publications
(52 reference statements)
2
32
0
4
Order By: Relevance
“…(See hypothesis IC3 below, which states that postdivorce conflict between parents lowers children's well-being.) Consistent with this interpretation, Hetherington, Cox, & Cox (1982) and Healy et al (1990) found that the frequency of father visitations was positively correlated with children's adjustment when interparental conflict was low but negatively correlated with children's adjustment when interparental conflict was high. The effects of contact are also likely to depend on the noncustodial parent's psychological adjustment and childrearing skills.…”
Section: Support For Hypothesesmentioning
confidence: 62%
“…(See hypothesis IC3 below, which states that postdivorce conflict between parents lowers children's well-being.) Consistent with this interpretation, Hetherington, Cox, & Cox (1982) and Healy et al (1990) found that the frequency of father visitations was positively correlated with children's adjustment when interparental conflict was low but negatively correlated with children's adjustment when interparental conflict was high. The effects of contact are also likely to depend on the noncustodial parent's psychological adjustment and childrearing skills.…”
Section: Support For Hypothesesmentioning
confidence: 62%
“…Several studies have found that frequent contact with the non-residential father is related to positive outcomes in offspring if interparental conflict is low and negative outcomes if conflict is high (Kelly, 2006). However, other studies have found a positive relation between father contact and youth adjustment in high conflict families up to five years post-divorce, suggesting that interparental conflict over the long term may not be detrimental if youth have frequent contact and a supportive relationship with the non-residential parent (Fabricius & Luecken, 2007; Healy, Malley, & Stewart, 1990; Kurdek, 1986). …”
Section: Non-residential Father Engagement and Youth Well-being: A Comentioning
confidence: 93%
“…The relationship between the two parents after divorce is extremely important. Many researchers have determined that it was the relationship after the divorce that was decisive (see, e.g., Healy, Malley, & Stewart, 1990;Johnston, Kline, & Tschann, 1989). When both parents maintain a calmer and less hostile and tension-charged relationship, the child can develop a reasonable and appropriate relationship with each of his or her parents, without feeling guilty about the other parent.…”
Section: The Decisions Of the Shari'a Court In This Specific Casementioning
confidence: 98%